Positive electrode material, preparation method thereof, positive electrode plate and secondary battery
By controlling the number of microcracks, unit cell volume and unit cell parameters in the positive electrode material of lithium-ion batteries, the problem of poor interface stability of existing positive electrode materials is solved, and higher cyclic stability and rate performance are achieved.
Patent Information
- Application Number
- CN202411967037.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-26
- Publication Date
- 2025-03-25
AI Technical Summary
The interface stability of existing lithium-ion battery cathode materials is poor, and there are problems of high gas production and poor circulation stability, which cannot meet the high energy density needs in new energy vehicles and other fields.
A new cathode material LixNiaCobMcNdO2 is provided. By controlling the number of microcracks, the unit cell volume V < 102.3 Å3, and the ratio of unit cell parameter c/a is greater than 4.95, it improves the gas production problem of the battery during storage and circulation, and improves the structural stability of the cathode material.
It effectively improves the circulation and rate performance of the battery, reduces the gas production of the positive electrode material at high voltage, improves the structural stability of the positive electrode material, and thus improves the overall performance of the battery.
Smart Images

Figure CN119695142A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of battery positive electrode materials, and in particular to a positive electrode material, a preparation method thereof, a positive electrode sheet and a secondary battery. Background Art
[0002] Currently, lithium-ion batteries are widely used in the field of new energy vehicles. However, their energy density is not high enough and the driving range of a single charge is short, which cannot meet the needs of the majority of automobile consumers. Therefore, it is urgent to further improve the energy density of lithium-ion batteries. As the core component of lithium-ion batteries, the development of positive electrode materials with higher specific energy is the key to improving the energy density of lithium-ion batteries.
[0003] However, existing cathode materials have poor interface stability, high gas generation and poor cycle stability. Summary of the invention
[0004] In view of this, in order to solve at least one of the above defects, it is necessary to provide a positive electrode material.
[0005] In addition, it is also necessary to provide a method for preparing the aforementioned positive electrode material, and a positive electrode sheet and a secondary battery using the aforementioned positive electrode material.
[0006] In a first aspect, the present invention provides a positive electrode material, the general formula of the positive electrode material is as follows: Li x Ni a Co b M c N d O2, M is Mn or Al, N is a metal element, wherein 0.98≤x≤1.1, 0.60≤a≤0.70, 0.06≤b≤0.12, 0.20<c≤0.32, 0<d≤0.10, a+b+c+d=1; the ratio of the number of particles with cracks in the positive electrode material to the total number of particles is 1.5%~11%, and the unit cell volume V of the positive electrode material is less than 102.3 Å 3 , the unit cell parameters satisfy: the ratio of c / a is greater than 4.95.
[0007] In some possible embodiments, the unit cell volume satisfies: 98.6 Å 3 <V<102.3 Å 3 , the unit cell parameters satisfy: 2.7584≤a≤2.8790 Å, 13.2865≤c≤14.2550 Å.
[0008] In some possible embodiments, the proportion of Li / Ni mixed in the positive electrode material is 5% to 8%.
[0009] In some possible embodiments, the lattice strain of the positive electrode material is less than 0.2%.
[0010] In some possible embodiments, the unit cell parameter Dp of the positive electrode material measured by XRD is 80nm~110nm.
[0011] In some possible embodiments, the positive electrode material is a single crystal positive electrode material, the positive electrode material contains single grains with the same orientation, and the average grain size of the single grains is 1 μm to 5 μm.
[0012] In some possible embodiments, the particle size distribution width of the positive electrode material satisfies L=(D90-D10) / D50≥1.0.
[0013] In some possible embodiments, the specific surface area of the positive electrode material is 0.5 m 2 / g ~1.2 m 2 / g.
[0014] In some possible embodiments, the tap density of the positive electrode material is ρ1>1.8 g / cm 3 .
[0015] In some possible embodiments, the compaction density of the positive electrode material is ρ2>3.00g / cm 3 .
[0016] In a second aspect, an embodiment of the present application provides a method for preparing a positive electrode material, comprising the following steps: mixing a nickel source, a cobalt source and a manganese source solution, and performing thermal decomposition after atomization treatment to obtain a precursor; mixing the precursor, a lithium source and a flux and sintering them to obtain a positive electrode material matrix; crushing the positive electrode material matrix, wherein the ratio of the number of particles with cracks in the crushed positive electrode material matrix to the total number of particles is 1.5%~11%; and coating the crushed positive electrode material matrix to obtain the positive electrode material, wherein the unit cell volume V of the positive electrode material is less than 102.3 Å 3 , the unit cell parameters satisfy: the ratio of c / a is greater than 4.95.
[0017] In a third aspect, an embodiment of the present application provides a positive electrode plate, comprising the positive electrode material as described above or a positive electrode material prepared by the method for preparing the positive electrode material as described above, wherein, in the positive electrode plate, the number of particles of the positive electrode material having the cracks accounts for 1.5% to 11% of the total number of particles of the positive electrode material.
[0018] In a fourth aspect, an embodiment of the present application provides a secondary battery, comprising a housing, an electrode assembly, and an electrolyte or an electrolyte, wherein the electrode assembly and the electrolyte or the electrolyte are both located within the housing, the electrode assembly comprises a separator and a negative electrode plate, the electrode assembly further comprises a positive electrode plate, the separator is disposed between the positive electrode plate and the negative electrode plate, and the positive electrode plate comprises the positive electrode material as described above.
[0019] The positive electrode material provided in the embodiment of the present application controls the proportion of microcracks in the positive electrode material to 1.5% to 11%, and the unit cell volume V is less than 102.3 Å. 3 , and the ratio of the unit cell parameter c / a is greater than 4.95, which can effectively improve the gas production problem of the battery during storage and cycling, while improving the structural stability of the positive electrode material, thereby improving the rate and cycle performance of the prepared battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 This is a schematic cross-sectional view of a lithium-ion battery using the positive electrode material of an embodiment of the present application during charging.
[0021] Figure 2 It is a schematic cross-sectional view of a lithium-ion battery using the positive electrode material of an embodiment of the present application during discharge.
[0022] Figure 3 This is a cross-sectional SEM image of the positive electrode material of Example 1 of the present application at a magnification of 5000 times.
[0023] Figure 4 This is a cross-sectional SEM image of the positive electrode material of Comparative Example 1 of the present application at a magnification of 5000 times. DETAILED DESCRIPTION
[0024] The embodiments of the present application are described in detail below. The embodiments described below with reference to the accompanying drawings are exemplary and are only used to explain the present application, and cannot be understood as limiting the present application; it should be noted that, unless otherwise defined, all technical and scientific terms used herein have the same meaning as those generally understood by technicians in the technical field of the present application; in the absence of conflict, the embodiments of the present application and the features in the embodiments can be combined with each other; many specific details are elaborated in the following description to facilitate a full understanding of the present application, and the described embodiments are only part of the embodiments of the present application, not all of the embodiments.
[0025] The present application provides a positive electrode material, the general formula of which is as follows: Li x Ni a Co b M c N dO2, M is Mn or Al, N is a metal element, wherein 0.98≤x≤1.1, 0.60≤a≤0.70, 0.06≤b≤0.12, 0.20<c≤0.32, 0<d≤0.10, a+b+c+d=1; the ratio of the number of particles with microcracks in the positive electrode material to the total number of particles is 1.5%~11%, and the unit cell volume V of the positive electrode material is less than 102.3 Å 3 , the unit cell parameters satisfy: the ratio of c / a is greater than 4.95. By controlling the crack ratio and unit cell volume of the positive electrode material, the problems of high gas generation and poor cycle stability of the positive electrode material under high voltage can be effectively improved.
[0026] First, the embodiment of the present application can effectively reduce the gas production of the positive electrode material during the battery cycle by controlling the number of cracks in the positive electrode material to account for 1.5% to 11%. When the number of cracks in the positive electrode material accounts for less than 1.5%, the crystal is too round, resulting in a low compaction density of the powder of this type of positive electrode material, which in turn leads to a low compaction density of the pole piece; when the number of cracks in the positive electrode material accounts for more than 11%, there are too many crystal cracks. After such positive electrode materials are prepared into batteries, the gas production of the battery will be significantly deteriorated during the cycle. Exemplarily, the number of cracks in the positive electrode material can account for 1.5%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, 11% or any value within the range of any two of the above values. It should be noted that the "crack" in this application refers to a crack with a width of less than 1um in the SEM image of the cross-section of the particle, so the crack can also be called a "microcrack".
[0027] Secondly, the present application controls the unit cell volume V of the cathode material to be less than 102.3 Å. 3 , which is conducive to stabilizing the crystal structure. The small unit cell volume means that the distance between atoms or ions in the unit cell is shorter, which enhances the interaction force between atoms or ions (such as Coulomb force, van der Waals force, etc.), thereby increasing the cohesive energy of the crystal. On the one hand, it can reduce the volume change of the material during the charging and discharging process and improve the cycle stability of the material. On the other hand, the higher cohesive energy requires the expansion of microcracks to overcome higher potential barriers, thereby inhibiting the diffusion of microcracks and further improving the cycle stability of the material. In addition, the small unit cell volume can also improve the particle strength and electronic conductivity. When the unit cell volume V ≥ 102.3Å3 of the positive electrode material, the strength and toughness of the lattice will be reduced, making the material prone to lattice defects when subjected to alternating stress, causing microcracks in the crystal, which may become sensitive points for electrochemical corrosion, increase the probability of side reactions with the electrolyte, and affect the cycle life of the battery. Furthermore, the unit cell volume of the positive electrode material satisfies: 98.6 Å 3 <V<102.3 Å 3 Furthermore, the unit cell volume of the cathode material satisfies: 98.6 Å3 <V<101.8 Å 3 By controlling the unit cell volume and unit cell parameters within the above range, the stability of the crystal structure can be further improved, thereby achieving further improvements in rate and cycle stability.
[0028] However, the process of lithium ion insertion or extraction will cause the expansion or contraction of the lattice, causing stress inside the unit cell, and a smaller unit cell volume also means that the same volume change will lead to greater local stress concentration; in addition, a too small unit cell matrix may be unfavorable for Li + Therefore, the present application further limits the ratio of the unit cell parameter c / a to be greater than 4.95. The larger the ratio of c / a, the fewer defects in the layered structure, which is beneficial to the transmission of lithium ions and improves the rate, reduces the lattice strain in the lithium ion conduction process caused by the small lattice volume, and thus compensates for the negative impact of the reduction in unit cell volume.
[0029] Therefore, this application controls the proportion of microcracks in the positive electrode material to 1.5%~11%, and the unit cell volume V is less than 102.3 Å. 3 , and the ratio of the unit cell parameter c / a is greater than 4.95, which can effectively improve the gas production problem of the positive electrode material, while improving the structural stability of the positive electrode material, thereby improving the cycle and rate performance of the material.
[0030] In some embodiments, the unit cell parameters of the positive electrode material satisfy: 2.7584≤a≤2.8790 Å, 13.2865≤c≤14.2550 Å.
[0031] In some embodiments, the proportion of Li / Ni mixed arrangement in the positive electrode material is 5% to 8%. Since the c value in the unit cell parameter is more sensitive to Li / Ni mixed arrangement, while the a value is not sensitive to mixed arrangement, and the c / a value of the positive electrode material is greater than 4.95, it indicates that the material has a highly ordered crystal structure and a low Li / Ni mixed arrangement ratio.
[0032] In some embodiments, the lattice strain of the positive electrode material is less than 0.2%. By controlling the ratio of the unit cell parameter c / a to be greater than 4.95, the larger the ratio of c / a, the fewer defects in the layered structure, which can effectively reduce the lattice strain in the lithium ion conduction process caused by the small lattice volume, so that the positive electrode material can maintain a small lattice strain under the premise of having a small unit cell volume. In addition, since it is difficult to completely eliminate the lattice strain in the positive electrode material, the lattice strain in the positive electrode material can be minimized by regulating the unit cell parameters in the embodiments of the present application. Furthermore, the lattice strain of the positive electrode material is 0.01%~0.2%.
[0033] In some embodiments, the unit cell parameter Dp of the positive electrode material measured by XRD is 80nm~110nm. The positive electrode material with the unit cell parameter Dp in the above range has higher discharge capacity and cycle performance. Exemplarily, the unit cell parameter Dp in the positive electrode material can be 80nm, 90nm, 100nm, 110nm or any value in the range composed of any two of the above values. It should be noted that the unit cell parameter Dp of the positive electrode material is measured by XRD using Cu-Kα rays, and Dp=D 003 +D 104 By measuring the diffraction angles corresponding to the (003) and (104) crystal plane diffraction peaks in the XRD spectrum, D can be calculated. 003 , D 104 The average value of the two is Dp.
[0034] In some embodiments, the width of the particle size distribution of the positive electrode material satisfies L=(D90-D10) / D50≥1.0. D10 in the particle size distribution represents the particle size corresponding to 10% of the volume cumulative particle size distribution, that is, in the particle population, 10% of the particles are smaller than this particle size. Usually, D10 is used to describe particles with finer particle sizes in the particle population. D90 represents the particle size corresponding to 90% of the volume cumulative particle size distribution, that is, in the particle population, 90% of the particles are smaller than this particle size. D90 is usually used to describe particles with coarser particle sizes in the particle population. (D90-D10) / D50 represents the width of the particle size distribution in the positive electrode material. In the present application, the particle size distribution of the positive electrode material satisfies (D90-D10) / D50≥1.0. The particle size distribution of the positive electrode material is moderate, which can reduce the specific surface area of the particles without reducing the compaction density of the material, thereby ensuring that the positive electrode material has a higher capacity. Further, 1.0≤(D90-D10) / D50≤1.6. Exemplarily, (D90-D10) / D50 may be 1.0, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6 or any value within the range of any two of the above values.
[0035] In some embodiments, the specific surface area of the positive electrode material is 0.5 m 2 / g~1.2 m 2 / g, the specific surface area of the positive electrode material is appropriate, which is conducive to reducing the direct contact between the positive electrode material and the electrolyte, thereby reducing the generation of side reactions, and is conducive to improving the cycle performance of the battery prepared using the positive electrode material, while also ensuring that the battery prepared using the positive electrode material has good rate performance. For example, the specific surface area of the positive electrode material can be 0.5 m 2 / g, 0.6 m 2 / g, 0.7 m 2 / g, 0.8 m 2 / g, 0.9 m 2 / g, 1.0m 2 / g, 1.1m 2 / g, 1.2 m 2 / g or any value within the range formed by any two of the above values.
[0036] In some embodiments, the tap density of the positive electrode material is ρ1>1.8 g / cm 3 The positive electrode material of the embodiment of the present application has a higher tap density, which means that there are more active substances per unit volume, thereby increasing the energy density of the prepared battery and enabling the battery to have a higher energy output capacity under the same volume. In addition, a higher tap density can improve the structural stability of the battery during the charge and discharge process, thereby improving the cycle stability of the battery. For example, the tap density ρ1 of the positive electrode material can be 1.8 g / cm 3 , 1.9g / cm 3 , 2.0g / cm 3 , 2.1g / cm 3 , 2.2g / cm 3 , 2.3g / cm 3 Or any value within the range formed by any two of the above values.
[0037] In some possible embodiments, the compaction density of the positive electrode material is ρ2>3.00g / cm 3 The positive electrode material of the embodiment of the present application has a high compaction density, so that the capacity and cycle performance of the battery prepared by using the positive electrode material can be improved. For example, the compaction density ρ2 of the positive electrode material can be 3.05 g / cm 3 、3.10g / cm 3 、3.15g / cm 3 、3.20g / cm 3 , 3.25g / cm 3 3.30g / cm 3 Or any value within the range formed by any two of the above values.
[0038] In some embodiments, the positive electrode material in the present application can be a nickel cobalt manganese oxide (NCM) ternary positive electrode material or a nickel cobalt aluminum oxide (NCA) ternary positive electrode material, depending on the type of the M element. At the same time, the N element is doped in the positive electrode material, which can optimize the crystal structure of the positive electrode material and further improve the stability of the crystal structure. It can also further improve the structural stability of the positive electrode material.
[0039] In some embodiments, Li x Ni a Cob M c N d O2, M is Mn or Al, N is a metal element, wherein 0.98≤x≤1.1, 0.60≤a≤0.70, 0.06≤b≤0.12, 0.20<c≤0.32, 0<d≤0.10, a+b+c+d=1.
[0040] The specific value of x can be 0.98, 0.99, 1.0, 1.02, 1.04, 1.05, 1.07, 1.08, 1.09 or 1.1, the specific value of a can be 0.6, 0.61, 0.62, 0.63, 0.64, 0.65, 0.66, 0.67, 0.68, 0.69, 0.7, etc., the value of b can be 0.06, 0.07, 0.08, 0.09, 0.1, 0.11, 0.12, etc., the value of c can be 0.20, 0.21, 022, 0.23, 0.25, 0.26, 0.27, 0.28, 0.29 or 0.32, etc., and there is no limitation on this. The value of d can be 0.02, 0.03, 0.04, 0.05, 0.07, 0.08, 0.09 or 0.10, etc.
[0041] In some embodiments, the N element includes at least one of Mn, Ti, Zr, Ca, Mg, W, Ba, La, Ce, B, and Y. It is understandable that an appropriate amount of M element doping can improve the lattice structure stability of the positive electrode material and reduce lithium-nickel mixing. The positive electrode material can be a nickel-cobalt-manganese oxide lithium compound or a nickel-cobalt-aluminum oxide lithium compound, which is not limited here.
[0042] In some embodiments, the aforementioned positive electrode material is a single crystal positive electrode material.
[0043] It should be noted that the difference between single crystal positive electrode materials and polycrystalline positive electrode materials (i.e., polycrystalline secondary particles) is that the smallest particle of polycrystalline secondary particles is a secondary particle formed by the agglomeration of nanometer-scale primary particles. For single crystal positive electrode materials, the smallest particle is usually a single primary particle of micrometer scale. Generally speaking, in addition to the EBSD test method, it is also possible to determine whether the obtained positive electrode product is a single crystal material by characterization methods such as scanning electron microscopy (SEM). For example, for single crystal positive electrode materials, the morphology of single crystal particles can be characterized by SEM, and it can be seen that the shape of single crystal particles is generally regular or irregular spherical, and there is no significant particle agglomeration. The orientation of single crystal positive electrode materials can also be characterized by EBSD. Through EBSD, it can be observed that the color in at least one grain is the same, so as to judge that the orientation in at least one grain is the same, and the grains with the same orientation are single crystals. It should be specifically noted that the "single crystal positive electrode material" known to those skilled in the art is not a "single crystal" in the strict crystallographic sense. In crystallography, an ideal single crystal refers to a crystal with completely the same arrangement and direction. However, due to impurities, strain and crystal defects, ideal single crystals are very rare and difficult to produce in the laboratory. Therefore, the single crystal positive electrode materials known in the art are actually more "single crystal morphology" positive electrode materials, which only show a large particle size similar to a single crystal in size, which is different from a polycrystal composed of many small primary particles. For ease of understanding, the single crystal positive electrode material involved in this application can be understood as a positive electrode material particle containing a single grain with the same orientation, and the average particle size of the above single grain is 1μm~5μm.
[0044] It can be understood that a single grain in the present application can be a single particle composed of a primary particle. The above-mentioned single crystal positive electrode material may also contain a small amount of "quasi-secondary particles" formed by the adhesion of several single particles. "Primary particle" refers to the smallest particle unit identified when observing the positive electrode active material through a scanning electron microscope, and "secondary particle" refers to a secondary structure formed by the agglomeration of multiple primary particles, showing a relatively rounded spherical morphology. "Quasi-secondary particles" refer to those formed by the adhesion of several single particles. Usually, the particle size of a single particle in the above-mentioned quasi-secondary particles is usually between 1um-5um. In general, the roundness of the particles of the "quasi-secondary particles" is lower than that of the above-mentioned conventional "secondary particles".
[0045] It should be further explained that the "single crystal" in the "single crystal positive electrode material" known to those skilled in the art is not a "single crystal" in the strict sense. In crystallography, an ideal single crystal refers to a crystal with exactly the same arrangement and direction. However, due to impurities, strain and crystal defects, ideal single crystals are very rare and difficult to produce in the laboratory. Therefore, the single crystal positive electrode materials known in the art are actually more of "single crystal-like morphology" positive electrode materials, which only show a large particle size similar to a single crystal in size, which is different from a polycrystal composed of many small primary particles.
[0046] Based on the same inventive concept, the present application also provides a method for preparing the aforementioned positive electrode material, which specifically comprises the following steps: Step S1, mixing solutions of a nickel source, a cobalt source and a manganese source, and performing thermal decomposition on the mixture after atomization to obtain a positive electrode material precursor.
[0047] Specifically, the solutions of nickel source, cobalt source and manganese source are mixed uniformly in a certain proportion, and then a complexing agent is added, atomized, and thermally decomposed to finally obtain a positive electrode material precursor. The material mixing can be carried out by ultrasonic mixing or other mixing methods to improve the mixing uniformity.
[0048] The nickel source, cobalt source and manganese source can be sulfate, hydrochloride, nitrate, acetate solution of the corresponding metal elements, etc. The precursor formed can be hydroxide, oxide, carbonate, phosphate, etc.
[0049] In some embodiments, the atomization flow rate is controlled to be 5 to 20 L / min. The flow rate affects the uniformity of the distribution of metal ions. A slow flow rate may cause the metal ions to segregate in the pipeline. A fast flow rate may cause uneven distribution of metal ions. By controlling the atomization flow rate, the various components in the mixture can be fully decomposed and evenly distributed. Further, the atomization flow rate can be 10 L / min to 15 L / min. Exemplarily, the atomization flow rate can be 5 L / min, 6 L / min, 7 L / min, 8 L / min, 9 L / min, 10 L / min, 11 L / min, 12 L / min, 13 L / min, 14 L / min, 15 L / min, 16 L / min, 17 L / min, 18 L / min, 19 L / min, 20 L / min or any value within the range composed of any two of the above values.
[0050] In some embodiments, the pyrolysis temperature T is controlled to be 550° C. to 1050° C. By regulating the pyrolysis temperature within the above range, the unit cell volume and unit cell parameters of the crystal can be adjusted.
[0051] In some embodiments, the pyrolysis temperature T and the atomized droplet diameter d (D50) are controlled to satisfy: T = (2000 + 600d) / (d + 2). The droplet size is positively correlated with the atomization temperature. The larger the droplet diameter D50, the higher the temperature T required for atomization, and a higher heat is required to atomize the droplets into powder particles. The atomized droplet diameter D50 plays a decisive role in the unit cell volume and unit cell parameters of the crystal. Therefore, by controlling the above relationship between the pyrolysis temperature T and the droplet diameter d (D50), the unit cell volume and unit cell parameters of the crystal can be regulated to meet the required standards. Among them, the atomized droplet diameter can be obtained by testing with a laser particle size analyzer.
[0052] In some embodiments, the main function of the complexing agent is to control the diameter d (D50) of the atomized droplets, which is beneficial to reduce the temperature required for spraying, reduce costs, and improve the uniformity of the solution. Different types of complexing agents can adjust the required diameters D50 of the atomized droplets. Specifically, the complexing agent can include phosphates, alcohol amines, aminocarboxylates, hydroxycarboxylates, organic phosphonates, and polyacrylic acid complexing agents, etc. The required type of complexing agent can be selected according to the required diameter of the atomized droplets. Among them, the addition of phosphate chelating agent will control the diameter D50 of the atomized droplets at 1μm~15μm, the addition of aminocarboxylate chelating agent will control the diameter D50 of the atomized droplets at 4μm~18μm, the addition of alcoholamine chelating agent will control the diameter D50 of the atomized droplets at 4μm~17μm, the addition of aminocarboxylate chelating agent will control the diameter D50 of the droplets at 8μm~16μm, the addition of organic phosphonate chelating agent will control the diameter D50 of the atomized droplets at 5μm~12μm, and the addition of polyacrylic acid chelating agent will control the diameter D50 of the atomized droplets at 8μm~20μm.
[0053] In some embodiments, the concentration of the complexing agent in the mixed solution is 0.2 mol / L to 3 mol / L. By controlling the concentration of the complexing agent within the above range, it is beneficial to further reduce the temperature required for spraying, reduce costs, control the diameter of the atomized droplets, and further improve the uniformity of the solution. Further, the concentration of the complexing agent can be 0.5 mol / L to 1.5 mol / L. Exemplarily, the concentration of the complexing agent can be 0.2 mol / L, 0.5 mol / L, 0.7 mol / L, 1 mol / L, 1.2 mol / L, 1.5 mol / L, 1.8 mol / L, 2 mol / L, 2.3 mol / L, 2.5 mol / L, 2.8 mol / L, 3 mol / L or any value within the range composed of any two of the above values.
[0054] In some embodiments, the complexing agent can be added twice, and the total time of adding the complexing agent twice can be 3h~18h, and the duration of the first and second additions of the complexing agent is 0.5h~6h. The time interval between the two additions of the complexing agent can be 0.5h~6h. By adding the complexing agent in batches, the diameter of the atomized droplets and the uniformity of the droplets can be increased, and it is also beneficial to control the concentration of the complexing agent. Exemplarily, the time interval between the two additions of the complexing agent can be 1h, 2h, 3h, 4h, 5h, 6h or any value within the range composed of any two of the above values. Exemplarily, the total time for adding the complexing agent can be 3h, 4h, 5h, 6h, 7h, 8h, 9h, 10h, 11h, 12h, 13h, 14h, 15h, 16h, 17h, 18h or any value within the range formed by any two of the above values, the duration of the first addition of the complexing agent can be 1h, 2h, 3h, 4h, 5h, 6h or any value within the range formed by any two of the above values, and the duration of the second addition of the complexing agent can be 1h, 2h, 3h, 4h, 5h, 6h or any value within the range formed by any two of the above values.
[0055] Step S2, mixing the positive electrode material precursor, lithium source and flux and sintering them to obtain a positive electrode material matrix.
[0056] Specifically, the precursor prepared in step S1 is preliminarily mixed with the lithium salt, and then a fluxing additive is added and uniformly mixed. Thereafter, the mixture is placed in an atmosphere furnace and calcined at a corresponding temperature and in a relevant atmosphere to obtain a positive electrode material matrix.
[0057] In this step, the flux will accelerate crystal growth in the early stage of sintering, reduce the sintering temperature of the crystal, and inhibit lithium-nickel mixing, thereby improving the material's first coulombic efficiency and discharge capacity; in the later stage of sintering, it will help to bridge the intercrystalline cracks of the crystal, resulting in the final sintered material becoming rounded and dispersed crystal particles.
[0058] In some embodiments, the flux may be a transition metal oxide with a low melting point, which is more conducive to the growth of crystals and the bridging of microcracks during the growth process. Specifically, the flux may contain at least one of Sr, W, Al, Ti, B, Ca and other elements.
[0059] In some embodiments, based on the positive electrode material precursor, the mass proportion of the flux can be 0.005wt%~0.8wt%. By controlling the mass proportion of the flux to not exceed 0.8wt%, the particle microcracks can be effectively improved. At the same time, due to the low addition ratio, it will not affect the content of the main elements in the positive electrode material, and the impact on the electrical properties of the positive electrode material is small. Exemplarily, the mass proportion of the flux can be 0.005wt%, 0.05wt%, 0.1wt%, 0.15wt%, 0.2wt%, 0.25wt%, 0.3wt%, 0.4wt%, 0.5wt%, 0.7wt%, 0.8wt% or any value within the range composed of any two of the above values.
[0060] In some embodiments, the lithium salt may be at least one of lithium hydroxide, lithium carbonate, lithium oxide, and lithium phosphate.
[0061] In this step, the positive electrode material matrix can be prepared by one-stage sintering or by multiple-stage sintering.
[0062] Among them, when one-stage sintering is adopted, the sintering temperature can be 850℃~980℃, and the sintering time can be 4h~12h. This sintering process can realize the melting of lithium salt and the infiltration of auxiliary materials into the precursor, and realize the formation and stabilization of crystal particles. By regulating the sintering temperature and sintering time within the aforementioned range, it can ensure that the crystal grows fully without over-sintering, thereby controlling the unit cell volume V<102.3 Å 3 , the ratio of the unit cell parameter c / a is greater than 4.95 to meet the required standards, thereby improving the particle strength and structural stability. Exemplarily, the sintering temperature can be 850°C, 860°C, 870°C, 880°C, 890°C, 900°C, 910°C, 920°C, 930°C, 940°C, 950°C, 960°C, 970°C, 980°C or any value within the range formed by any two of the above values. Exemplarily, the sintering time can be 4h, 5h, 6h, 7h, 8h, 9h, 10h, 11h, 12h or any value within the range formed by any two of the above values.
[0063] When multi-stage sintering is adopted, the sintering process may include a first sintering stage, a second sintering stage and a third sintering stage which are carried out in sequence. Among them, the sintering temperature of the first sintering stage is 300℃~600℃, and the sintering time is 1h~3h. The material is first heated to a lower temperature stage, which can fully melt the lithium salt and evenly diffuse the flux in the mixture, which is more conducive to bridging the intercrystalline cracks of the crystal, so that the final sintered material becomes rounded and dispersed crystal particles. The sintering temperature of the second sintering stage is 700℃~880℃, and the sintering time is 1h~3h. The temperature is raised and crystals are formed. By controlling the sintering temperature and sintering time within the above range, the embedding of lithium ions can be achieved, promoting a certain degree of crystal growth, and controlling the rate and size of the crystal particle size growth. The sintering temperature of the third sintering stage is 900℃~1000℃, and the sintering time is 6h~12h. This stage is the main stage of crystal growth. By controlling the sintering temperature and sintering time within the aforementioned range, the unit cell volume V of the crystal particles can be controlled to be less than 102.3 Å. 3 , the ratio of the unit cell parameter c / a is greater than 4.95 to meet the required standards, thereby improving the strength and structural stability of the crystal particles. Finally, rapid annealing and cooling are carried out at a cooling rate of 5℃ / min~10℃ / min to obtain the positive electrode material matrix. Rapid annealing and cooling can further repair intergranular cracks, thereby further reducing the proportion of microcracks in the particles.
[0064] In some embodiments, additives other than the aforementioned flux may be added to the mixture, wherein the elements in the additives may include at least one of Al, Ti, Mg, Ba, Sn, Mo, W, Sb, Ta, Sn, and Y. By doping the ternary positive electrode material with elements, the crystal structure of the positive electrode material may be optimized, and the stability of the crystal structure may be further improved. The structural stability of the positive electrode material may also be further improved.
[0065] Step S3, crushing the cathode material matrix, wherein the number of particles with microcracks in the crushed cathode material matrix accounts for 1.5% to 11% of the total number of particles, and the unit cell volume V of the cathode material is less than 102.3 Å 3 , the unit cell parameters satisfy: the ratio of c / a is greater than 4.95.
[0066] Specifically, the product of the primary sintering in step S2 is subjected to air flow pulverization. The pulverization process parameters are controlled to adjust the proportion of microcracks in the particles, thereby controlling the proportion of microcracks in the primary sintered pulverized material to 1.5% to 11%.
[0067] In some embodiments, the mass of the mill body is 20% to 60% of the upper limit of the sample volume processed by the device, and the filling volume is 15% to 30% of the mill body bin. For example, the upper limit of the sample volume processed by a small airflow pulverizer is 2 kg, and the mass of the mill body is 0.4 kg to 1.2 kg. Within this range of the mass of the mill body, the particles can be evenly dispersed, so as not to produce microcracks due to excessive collision of particles, and the efficiency of airflow crushing can be ensured. The mass of the mill body is further 20% to 50% of the upper limit of the device. Exemplarily, the mass of the mill body can be 20%, 30%, 40%, 50%, 60% of the upper limit of the device, or any value within the range formed by any two of the above values, that is, the mass of the mill body can be 400g, 500g, 600g, 700g, 800g, 900g, 1000g, 1100g, 1200g, or any value within the range formed by any two of the above values.
[0068] In some embodiments, the crushing gas pressure is controlled to be 0.4Mpa to 0.65Mpa. Within this range, the crushing gas pressure is moderate, so that too much microcracks are not generated due to strong collisions caused by excessive crushing gas pressure, and too little crushing pressure causes insufficient collisions between particles, thereby causing the particles to not be dispersed. Exemplarily, the crushing gas pressure can be 0.4Mpa, 0.45Mpa, 0.5Mpa, 0.55Mpa, 0.6Mpa, 0.65Mpa, or any value within the range formed by any two of the above values.
[0069] In some embodiments, the specific surface area of the crushed material is controlled to be 0.8 m 2 / g or less.
[0070] Step S4, coating the crushed positive electrode material matrix to obtain the positive electrode material.
[0071] The positive electrode material matrix is subjected to a coating post-treatment, and the coating post-treatment process is a low-temperature sintering process, the purpose of which is to uniformly coat the coating agent on the surface of the positive electrode material matrix for surface modification, so as to further improve the structural stability and electrochemical performance of the positive electrode material.
[0072] In some embodiments, the coating treatment temperature is 450° C. to 750° C., and the coating treatment time is 4 h to 10 h.
[0073] In some embodiments, the coating element contained in the coating agent includes at least one of Al, Ti, Zr, Y, Co, W, La, Nb, and Mo. Exemplarily, the coating treatment temperature is 450°C, 500°C, 550°C, 600°C, 650°C, 700°C, 750°C, or any value within the range formed by any two of the above values. Exemplarily, the sintering time can be 4h, 5h, 6h, 7h, 8h, 9h, 10h, or any value within the range formed by any two of the above values.
[0074] The preparation method of the positive electrode material of the embodiment of the present application controls the generation of microcracks inside the particles and on the internally connected surfaces by improving the sintering process and the gas crushing process, so that the ratio of the number of particles with microcracks in the positive electrode material to the total number of particles is 1.5% to 11%, thereby improving the gas generation problem of the high-voltage application of the positive electrode material; and controls the unit cell volume of the positive electrode material prepared by spray pyrolysis by controlling the sintering process, so that the unit cell volume V is less than 102.3 Å 3 , the unit cell parameters satisfy: the ratio of c / a is greater than 4.95, so that the positive electrode material prepared by spray pyrolysis has a good cycle life while maintaining high rate performance. Therefore, the preparation process of the positive electrode material is simple, the obtained positive electrode particles have few microcracks, the gas generation is low during storage and circulation at high voltage, and it can effectively improve the rate and cycle stability of the prepared battery.
[0075] The embodiment of the present application also provides a positive electrode sheet using the above positive electrode material, comprising a positive electrode current collector and a positive electrode active material layer provided on at least one surface of the positive electrode current collector, wherein the positive electrode active material layer comprises the above positive electrode material. In the positive electrode sheet, the number of particles of the positive electrode material having the cracks accounts for 1.5% to 11% of the total number of particles of the positive electrode material.
[0076] The positive electrode current collector may be aluminum foil or nickel foil, or any composite current collector disclosed in the prior art, such as but not limited to a current collector formed by combining the aforementioned conductive foil and a polymer substrate.
[0077] The present application also provides a secondary battery (such as a lithium-ion battery, a sodium-ion battery, etc.), including a housing, an electrode assembly and an electrolyte / electrolyte. The electrode assembly and the electrolyte / electrolyte are both located in the housing. The electrode assembly includes a separator, a negative electrode sheet and the positive electrode sheet, and the separator is disposed between the positive electrode sheet and the negative electrode sheet.
[0078] In some embodiments, the outer shell may be a packaging bag encapsulated by an encapsulation film (such as an aluminum-plastic film), such as a soft-pack battery. In other embodiments, the secondary battery may also be a steel-shell battery, an aluminum-shell battery, or the like.
[0079] In some embodiments, the electrode assembly may be a laminated structure, which is formed by alternately stacking a positive electrode sheet, a separator, and a negative electrode sheet. In other embodiments, the electrode assembly may also be a wound structure, which is formed by stacking a positive electrode sheet, a separator, and a negative electrode sheet in sequence and then winding them.
[0080] In some embodiments, the negative electrode sheet includes a negative electrode current collector and a negative electrode active material layer disposed on at least one surface of the negative electrode current collector. The negative electrode current collector may use at least one of copper foil, nickel foil, stainless steel foil, titanium foil or carbon-based current collector, etc., or may be a composite current collector disclosed in any prior art, such as but not limited to the current collector formed by combining the aforementioned conductive foil and polymer substrate. The negative electrode active material may include at least one of the following materials: artificial graphite, natural graphite, soft carbon, hard carbon, silicon-based materials, tin-based materials and lithium titanate, etc. The silicon-based material may be selected from at least one of elemental silicon, silicon oxide compounds, silicon-carbon composites, silicon-nitrogen composites and silicon alloys. The tin-based material may be selected from at least one of elemental tin, tin oxide compounds and tin alloys. However, the present application is not limited to these materials, and other traditional materials that can be used as negative electrode active materials for batteries may also be used. These negative electrode active materials may be used alone or in combination of two or more. The battery provided in the embodiment of the present application has the advantages of high capacity, high initial efficiency, long cycle life, excellent rate performance and low expansion. The battery can be a lithium-ion battery, a sodium-ion battery, a solid electrolyte battery, etc., without limitation herein.
[0081] like Figure 1 and Figure 2 As shown in the figure, they are schematic diagrams of lithium removal and lithium insertion during the charging and discharging process of a lithium-ion battery prepared by using the positive electrode material provided in the embodiment of the present application. Figure 1 As shown in , when a lithium-ion battery is charged, lithium ions are released from the positive electrode and embedded in the negative electrode; Figure 2 As shown, when a lithium-ion battery is discharged, lithium ions are released from the negative electrode and embedded back into the positive electrode.
[0082] In the embodiment of the present application, the proportion of particles with microcracks in the positive electrode material is controlled to be 1.5% to 11%, and the unit cell volume V is less than 102.3 Å. 3 , and the ratio of the unit cell parameter c / a is greater than 4.95, which can effectively improve the gas production problem of the battery during storage and cycling, while improving the structural stability of the positive electrode material, thereby improving the cycle and rate performance of the prepared battery.
[0083] The scheme of the present application will be explained below in conjunction with the embodiments. Those skilled in the art will understand that the following examples are only used to explain the present application and cannot be construed as limiting the present application. Unless otherwise stated, the reagents, software and instruments not specifically stated in the following embodiments are all conventional commercial products or open source.
[0084] Example 1 Step S1, dissolving metal nickel, cobalt and manganese in nitric acid at a molar ratio of 65:10:25 to form a uniform metal mixed solution, ultrasonically dispersing the metal mixed solution for 2 hours, and then adding ammonium carbamate as a complexing agent in two times, with a total addition time of 3 hours, a 0.5 hour interval between the two times, a first continuous addition time of 1.5 hours, and a second continuous addition time of 1 hour, and finally the concentration of ammonium carbamate in the metal mixed solution is 2 mol / L; spraying the metal mixed solution, controlling the atomization flow rate to 15 L / min, controlling the median particle size D50 of the droplets to 10 μm, and the atomization temperature to 667°C, to obtain a precursor Ni 0.65 Co 0.1 Mn 0.25 O x (0.8<x<1.2).
[0085] Step S2, weigh 500 g of the above oxide precursor, mix it evenly with 273.4 g of LiOH·H2O and 1.2 g of Al2O3, and sinter the mixture in an oxygen atmosphere furnace at 940° C. for 8 h to obtain a positive electrode material matrix.
[0086] Step S3, the positive electrode material matrix is subjected to air flow pulverization, the grinding mass is controlled at 400 g, the air pressure is controlled at 0.65 MPa, and the specific surface area of the obtained particles is 0.6 m 2 / g.
[0087] Step S4, 100g of the crushed positive electrode material matrix was mixed with 0.2g of TiO2, sintered in an oxygen atmosphere furnace at 550°C for 5h, and the positive electrode material (LiNi 0.65 Co 0.1 Mn 0.25 O2).
[0088] Example 2 Step S1, dissolving metal nickel, cobalt and manganese in hydrochloric acid at a molar ratio of 60:10:30 to form a uniform metal mixed solution, ultrasonically dispersing the metal mixed solution for 2 hours, and then adding alcohol amine as a complexing agent, adding it twice, the adding time is 3 hours, the interval between the two times is 1 hour, the first continuous adding time is 1 hour, and the second continuous adding time is 1 hour, and the final concentration of alcohol amine in the metal mixed solution is 0.8 mol / L; spraying granulation of the metal mixed solution, controlling the atomization flow rate to 12 L / min, controlling the median particle size D50 of the droplets to 12 μm, and the atomization temperature to 657 ° C, to obtain a positive electrode material precursor Ni 0.6 Co 0.1 Mn 0.3 O x(0.8<x<1.2).
[0089] Step S2, weigh 200 g of the above oxide precursor, mix it evenly with 94.8 g of Li2CO3 and 0.4 g of W2O3, and sinter the mixture in an oxygen atmosphere furnace at 960° C. for 8 hours to obtain a positive electrode material matrix.
[0090] Step S3, the positive electrode material matrix is subjected to air flow pulverization, the grinding mass is controlled at 1200 g, the air pressure is controlled at 0.65 MPa, and the specific surface area of the obtained particles is 0.7 m 2 / g.
[0091] Step S4, 100g of the crushed positive electrode material matrix was mixed with 0.2g of ZrO2, and sintered in an oxygen atmosphere furnace at 500°C for 5h, and the positive electrode material (LiNi 0.6 Co 0.1 Mn 0.3 O2).
[0092] Example 3 Step S1, dissolving metal nickel, cobalt and manganese in hydrochloric acid at a molar ratio of 60:10:30 to form a uniform metal mixed solution, ultrasonically dispersing the metal mixed solution for 2 hours, and then adding alcohol amine as a complexing agent, adding it twice, the adding time is 3 hours, the interval between the two times is 1 hour, the first continuous adding time is 0.5 hours, and the second continuous adding time is 1.5 hours, and the final concentration of alcohol amine in the metal mixed solution is 1 mol / L; spraying granulation of the metal mixed solution, controlling the atomization flow rate to 10 L / min, controlling the median particle size D50 of the droplets to 11 μm, and the atomization temperature to 662 ° C, to obtain a positive electrode material precursor Ni 0.6 Co 0.1 Mn 0.3 O x (0.8<x<1.2).
[0093] Step S2, weigh 500g of the above oxide precursor, mix it evenly with 220g of Li2CO3 and 2.4g of W2O3, and sinter the mixture in an oxygen atmosphere furnace at 940°C for 8h to obtain a positive electrode material matrix.
[0094] Step S3, the positive electrode material matrix is subjected to air flow pulverization, the grinding mass is controlled at 400 g, the air pressure is controlled at 0.40 MPa, and the specific surface area of the obtained particles is 0.6 m 2 / g.
[0095] Step S4, 200g of the crushed positive electrode material matrix was mixed with 0.3g of ZrO2, and sintered in an oxygen atmosphere furnace at 700°C for 5h, and the positive electrode material (LiNi 0.6 Co0.1 Mn 0.3 O2).
[0096] Example 4 Step S1, dissolving the metal sulfates of nickel, cobalt and manganese in water according to a molar ratio of 67:5:28 to form a uniform metal mixed solution, ultrasonically dispersing the metal mixed solution for 2 hours, and then adding ammonium carbamate as a complexing agent, adding it twice, the adding time is 3.5 hours, the interval between the two times is 0.5 hours, the first continuous adding time is 2 hours, and the second continuous adding time is 1 hour, and the final concentration of ammonium carbamate in the metal mixed solution is 0.6 mol / L; spraying granulation of the metal mixed solution, controlling the atomization flow rate to 15 L / min, controlling the median particle size D50 of the droplets to 12 μm, and the atomization temperature to 657 ° C, to obtain a positive electrode material precursor Ni 0.67 Co 0.05 Mn 0.28 O x (0.8<x<1.2).
[0097] Step S2, weigh 500 g of the above oxide precursor, mix it with 210 g of Li2CO3 and 1.9 g of SrO evenly, and sinter the mixture in an oxygen atmosphere furnace at 940° C. for 8 hours to obtain a positive electrode material matrix.
[0098] Step S3, the positive electrode material matrix is subjected to air flow pulverization, the grinding mass is controlled at 1200 g, the air pressure is controlled at 0.50 MPa, and the specific surface area of the obtained particles is 0.7 m 2 / g.
[0099] Step S4, 200g of the crushed positive electrode material matrix was mixed with 0.3g of ZrO2, and sintered in an oxygen atmosphere furnace at 700°C for 5h, and the positive electrode material (LiNi 0.67 Co 0.05 Mn 0.28 O2).
[0100] Example 5 Step S1, dissolving the metal sulfates of nickel, cobalt and manganese in water according to a molar ratio of 65:7:28 to form a uniform metal mixed solution, ultrasonically dispersing the metal mixed solution for 2 hours, and then adding ammonium carbamate as a complexing agent, adding it twice, the adding time is 4 hours, the interval between the two times is 2 hours, the first continuous adding time is 1 hour, and the second continuous adding time is 1 hour, and the final concentration of ammonium carbamate in the metal mixed solution is 2 mol / L; spraying the metal mixed solution, controlling the atomization flow rate to 16 L / min, controlling the median particle size D50 of the droplets to 8 μm, and the atomization temperature to 680 ° C, to obtain a positive electrode material precursor Ni 0.65 Co0.07 Mn 0.28 O x (0.8<x<1.2).
[0101] Step S2, weigh 500 g of the above oxide precursor, mix it evenly with 240 g of LiOH·H2O and 2.5 g of SrCO3, and sinter the mixture in an oxygen atmosphere furnace at 940° C. for 8 hours to obtain a positive electrode material matrix.
[0102] Step S3, the positive electrode material matrix is subjected to air flow pulverization, the grinding mass is controlled at 800 g, the air pressure is controlled at 0.50 MPa, and the specific surface area of the obtained particles is 0.7 m 2 / g.
[0103] Step S4, 200g of the crushed positive electrode material matrix was mixed with 0.6g of Al2O3, and sintered in an oxygen atmosphere furnace at 700°C for 5h, and the positive electrode material (LiNi 0.65 Co 0.07 Mn 0.28 O2).
[0104] Example 6 Step S1, dissolving the metal sulfates of nickel, cobalt and manganese in water according to a molar ratio of 65:7:28 to form a uniform metal mixed solution, ultrasonically dispersing the metal mixed solution for 2 hours, and then adding alcohol amine as a complexing agent, adding it twice, the adding time is 3 hours, the interval between the two times is 1 hour, the first continuous adding time is 1 hour, and the second continuous adding time is 1 hour, and the final concentration of alcohol amine in the metal mixed solution is 1.5 mol / L; spraying granulation of the metal mixed solution, controlling the atomization flow rate to 8 L / min, controlling the median particle size D50 of the droplets to 5 μm, and the atomization temperature to 715 ° C, to obtain a positive electrode material precursor Ni 0.65 Co 0.07 Mn 0.28 O x (0.8<x<1.2).
[0105] Step S2, weigh 500 g of the above oxide precursor, mix it evenly with 240 g of LiOH·H2O and 2.5 g of SrCO3, and sinter the mixture in an oxygen atmosphere furnace at 940° C. for 10 hours to obtain a positive electrode material matrix.
[0106] Step S3, the positive electrode material matrix is subjected to air flow pulverization, the grinding mass is controlled at 400 g, the air pressure is controlled at 0.50 MPa, and the specific surface area of the obtained particles is 0.6 m 2 / g.
[0107] Step S4, 200g of the crushed positive electrode material matrix was mixed with 0.6g of Al2O3, sintered in an oxygen atmosphere furnace at 700°C for 6h, and the positive electrode material (LiNi 0.65 Co 0.07 Mn 0.28 O2).
[0108] Example 7 Step S1, dissolving the metal sulfates of nickel, cobalt and manganese in water according to a molar ratio of 60:10:30 to form a uniform metal mixed solution, ultrasonically dispersing the metal mixed solution for 2 hours, and then adding sodium aminocarboxylate as a complexing agent, adding twice, the adding time is 3 hours, the interval between the two times is 1 hour, the first continuous adding time is 1 hour, and the second continuous adding time is 1 hour, and the final concentration of sodium aminocarboxylate in the metal mixed solution is 1.5 mol / L; spraying the metal mixed solution, controlling the atomization flow rate to 12 L / min, controlling the median particle size D50 of the droplets to 15 μm, and the atomization temperature to 647 ° C, to obtain a positive electrode material precursor Ni 0.6 Co 0.1 Mn 0.3 O x (0.8<x<1.2).
[0109] Step S2, weigh 500 g of the above oxide precursor, 240 g of LiOH·H2O, and 2.5 g of WO3, mix them evenly, and sinter the mixture in an oxygen atmosphere furnace at 960° C. for 10 hours to obtain a positive electrode material matrix.
[0110] Step S3, the positive electrode material matrix is subjected to air flow pulverization, the grinding mass is controlled at 800 g, the air pressure is controlled at 0.50 MPa, and the specific surface area of the obtained particles is 0.65 m 2 / g.
[0111] Step S4, 200g of the crushed positive electrode material matrix was mixed with 0.6g of Al2O3, and sintered in an oxygen atmosphere furnace at 700°C for 5h, and the positive electrode material (LiNi 0.6 Co 0.1 Mn 0.3 O2).
[0112] Example 8 Step S1, dissolving the metal sulfates of nickel, cobalt and manganese in water according to a molar ratio of 60:10:30 to form a uniform metal mixed solution, ultrasonically dispersing the metal mixed solution for 2 hours, and then adding sodium aminocarboxylate as a complexing agent, adding twice, the adding time is 3 hours, the interval between the two times is 1 hour, the first continuous adding time is 1 hour, and the second continuous adding time is 1 hour, and the final concentration of sodium aminocarboxylate in the metal mixed solution is 1.2 mol / L; spraying the metal mixed solution, controlling the atomization flow rate to 18 L / min, controlling the median particle size D50 of the droplets to 14 μm, and the atomization temperature to 650 ° C, to obtain a positive electrode material precursor Ni 0.6 Co 0.1 Mn 0.3 O x (0.8<x<1.2).
[0113] Step S2, weigh 500 g of the above oxide precursor, 240 g of LiOH·H2O, and 2.5 g of WO3, mix them evenly, and sinter the mixture in an oxygen atmosphere furnace at 960° C. for 8 hours to obtain a positive electrode material matrix.
[0114] Step S3, the positive electrode material matrix is subjected to air flow pulverization, the grinding mass is controlled at 1200 g, the air pressure is controlled at 0.40 MPa, and the specific surface area of the obtained particles is 0.65 m 2 / g.
[0115] Step S4, 200g of the crushed positive electrode material matrix was mixed with 0.6g of Al2O3, and sintered in an oxygen atmosphere furnace at 700°C for 8h, and the positive electrode material (LiNi 0.6 Co 0.1 Mn 0.3 O2).
[0116] Example 9 Step S1, dissolving metal nickel, cobalt and manganese in nitric acid at a molar ratio of 65:10:25 to form a uniform metal mixed solution, ultrasonically dispersing the metal mixed solution for 2 hours, and then adding alcohol amine as a complexing agent, adding it twice, the adding time is 3.5 hours, the interval between the two times is 1 hour, the first continuous adding time is 1 hour, and the second continuous adding time is 1.5 hours, and the final concentration of alcohol amine in the metal mixed solution is 0.9 mol / L; spraying granulation of the metal mixed solution, controlling the atomization flow rate to 12 L / min, controlling the median particle size D50 of the droplets to 10 μm, and the atomization temperature to 667 ° C, to obtain a positive electrode material precursor Ni 0.65 Co 0.1 Mn 0.25 O x (0.8<x<1.2).
[0117] Step S2, weigh 500g of the above oxide precursor and mix them evenly with 273.4g LiOH·H2O and 2.5g WO3, and adopt three-stage sintering with temperatures of 500℃ / 1.5h, 800℃ / 2h, and 940℃ / 8h respectively, and quickly anneal and cool down with a cooling rate of 5℃ / min to obtain a positive electrode material matrix.
[0118] Step S3, the positive electrode material matrix is subjected to air flow pulverization, the grinding mass is controlled at 400 g, the air pressure is controlled at 0.4 MPa, and the specific surface area of the obtained particles is 0.5 m 2 / g.
[0119] Step S4, 100g of the crushed positive electrode material matrix was mixed with 0.2g of TiO2, sintered in an oxygen atmosphere furnace at 550°C for 5h, and the positive electrode material (LiNi 0.65 Co 0.1 Mn 0.25 O2).
[0120] Example 10 Step S1, dissolving metal nickel, cobalt and manganese in nitric acid in a molar ratio of 65:10:25 to form a uniform metal mixed solution, ultrasonically dispersing the metal mixed solution for 2 hours, and then adding sodium aminocarboxylate as a complexing agent, adding it twice, the adding time is 3 hours, the interval between the two times is 1 hour, the first continuous adding time is 1 hour, and the second continuous adding time is 1 hour, and the final concentration of sodium aminocarboxylate in the metal mixed solution is 2 mol / L; spraying granulation of the metal mixed solution, controlling the atomization flow rate to 20 L / min, controlling the median particle size D50 of the droplets to 16 μm, and the atomization temperature to 645 ° C, to obtain a positive electrode material precursor Ni 0.65 Co 0.1 Mn 0.25 O x (0.8<x<1.2).
[0121] Step S2, weigh 500 g of the above oxide precursor, mix it with 273.4 g of LiOH·H2O and 2.2 g of TiO2 evenly, and sinter the mixture in an oxygen atmosphere furnace at 940° C. for 8 hours to obtain a positive electrode material matrix.
[0122] Step S3, the positive electrode material matrix is subjected to air flow pulverization, the grinding mass is controlled at 1200 g, the air pressure is controlled at 0.65 MPa, and the specific surface area of the obtained particles is 0.75 m 2 / g.
[0123] Step S4, 100g of the crushed positive electrode material matrix was mixed with 0.2g of TiO2, sintered in an oxygen atmosphere furnace at 550°C for 5h, and the positive electrode material (LiNi0.65 Co 0.1 Mn 0.25 O2).
[0124] Embodiment 11 Step S1, dissolving metal nickel, cobalt and manganese in nitric acid in a molar ratio of 65:10:25 to form a uniform metal mixed solution, ultrasonically dispersing the metal mixed solution for 2 hours, and then adding potassium phosphonate as a complexing agent, adding it twice, the addition time is 2 hours, the interval between the two times is 0.5 hours, the first continuous addition time is 1 hour, and the second continuous addition time is 0.5 hours, and the final concentration of potassium phosphonate in the metal mixed solution is 1.5 mol / L; spraying granulation of the metal mixed solution, controlling the atomization flow rate to 10 L / min, controlling the median particle size D50 of the droplets to 7 μm, and the atomization temperature to 845 ° C, to obtain a positive electrode material precursor Ni 0.65 Co 0.1 Mn 0.25 O x (0.8<x<1.2).
[0125] Step S2, weigh 500g of the above oxide precursor and mix them evenly with 273.4g LiOH·H2O and 1.2g Al2O3, and adopt three-stage sintering with temperatures of 500℃ / 2h, 600℃ / 3h, and 940℃ / 10h respectively, and quickly anneal and cool down with a cooling rate of 8℃ / min to obtain a positive electrode material matrix.
[0126] Step S3, the positive electrode material matrix is subjected to air flow pulverization, the grinding mass is controlled at 400 g, the air pressure is controlled at 0.65 MPa, and the specific surface area of the obtained particles is 0.6 m 2 / g.
[0127] Step S4, 100g of the crushed positive electrode material matrix was mixed with 0.2g of TiO2, sintered in an oxygen atmosphere furnace at 550°C for 5h, and the positive electrode material (LiNi 0.65 Co 0.1 Mn 0.25 O2).
[0128] Example 12 Step S1, dissolving metal nickel, cobalt and manganese in nitric acid in a molar ratio of 65:10:25 to form a uniform metal mixed solution, ultrasonically dispersing the metal mixed solution for 2 hours, and then adding potassium phosphonate as a complexing agent, adding it twice, the addition time is 2 hours, the interval between the two times is 1 hour, the first continuous addition time is 0.5 hours, and the second continuous addition time is 0.5 hours. The final concentration of potassium phosphonate in the metal mixed solution is 2.5 mol / L; spraying granulation of the metal mixed solution, controlling the atomization flow rate to 14 L / min, controlling the median particle size D50 of the droplets to 9 μm, and the atomization temperature to 673 ° C, to obtain a positive electrode material precursor Ni 0.65 Co 0.1 Mn 0.25 O x (0.8<x<1.2).
[0129] Step S2, weigh 500g of the above oxide precursor and mix them evenly with 273.4g LiOH·H2O and 1.2g Al2O3, and adopt three-stage sintering with temperatures of 600℃ / 2h, 800℃ / 2h, and 940℃ / 8h respectively, and quickly anneal and cool down with a cooling rate of 10℃ / min to obtain a positive electrode material matrix.
[0130] Step S3, the positive electrode material matrix is subjected to air flow pulverization, the grinding mass is controlled at 400 g, the air pressure is controlled at 0.65 MPa, and the specific surface area of the obtained particles is 0.6 m 2 / g.
[0131] Step S4, 100g of the crushed positive electrode material matrix was mixed with 0.2g of TiO2, sintered in an oxygen atmosphere furnace at 550°C for 5h, and the positive electrode material (LiNi 0.65 Co 0.1 Mn 0.25 O2).
[0132] Comparative Example 1 Step S1, dissolving metal nickel, cobalt and manganese in nitric acid at a molar ratio of 65:10:25 to form a uniform metal mixed solution, spraying and granulating the metal mixed solution, controlling the atomization flow rate to 10 L / min, controlling the median particle size D50 of the droplets to 12 μm, and the atomization temperature to 657°C to obtain the positive electrode material precursor Ni 0.65 Co 0.1 Mn 0.25 O x (0.8<x<1.2).
[0133] Step S2, weigh 500 g of the above oxide precursor and mix it evenly with 232 g of LiOH·H2O, and sinter the mixture in an oxygen atmosphere furnace at 940° C. for 8 h to obtain a positive electrode material matrix.
[0134] Step S3, the positive electrode material matrix is subjected to air flow pulverization, the grinding mass is controlled at 2000 g, the air pressure is controlled at 0.5 MPa, and the specific surface area of the obtained particles is 0.9 m 2 / g.
[0135] Step S4, 100g of the crushed positive electrode material matrix was mixed with 0.2g of TiO2, sintered in an oxygen atmosphere furnace at 550°C for 5h, and the positive electrode material (LiNi 0.65 Co 0.1 Mn 0.25 O2).
[0136] Comparative Example 2 Step S1, dissolving metal nickel, cobalt and manganese in nitric acid at a molar ratio of 60:10:30 to form a uniform metal mixed solution, spraying and granulating the metal mixed solution, controlling the atomization flow rate to 10 L / min, controlling the median particle size D50 of the droplets to 12 μm, and the atomization temperature to 657°C to obtain the positive electrode material precursor Ni 0.6 Co 0.1 Mn 0.3 O x (0.8<x<1.2).
[0137] Step S2, weigh 200 g of the above oxide precursor and mix it evenly with 93.8 g of LiOH·H2O, and sinter the mixture in an oxygen atmosphere furnace at 960° C. for 10 hours to obtain a positive electrode material matrix.
[0138] Step S3, the positive electrode material matrix is subjected to air flow pulverization, the grinding mass is controlled at 400 g, the air pressure is controlled at 0.7 MPa, and the specific surface area of the obtained particles is 1.0 m 2 / g.
[0139] Step S4, 100g of the crushed positive electrode material matrix was mixed with 0.2g of Al2O3, sintered in an oxygen atmosphere furnace at 500°C for 6h, and the positive electrode material (LiNi 0.6 Co 0.1 Mn 0.3 O2).
[0140] Comparative Example 3 Step S1, dissolving metal nickel, cobalt and manganese in nitric acid at a molar ratio of 65:15:20 to form a uniform metal mixed solution, spraying and granulating the metal mixed solution, controlling the atomization flow rate to 10 L / min, controlling the median particle size D50 of the droplets to 12 μm, and the atomization temperature to 657°C to obtain the positive electrode material precursor Ni 0.65 Co 0.15 Mn 0.2 Ox (0.8<x<1.2).
[0141] Step S2, weigh 500g of the above oxide precursor and mix it evenly with 220g of Li2CO3, and sinter the mixture in an oxygen atmosphere furnace at 950°C for 8h to obtain a positive electrode material matrix.
[0142] Step S3: Grind the cathode material matrix by air flow, control the grinding mass to 2000 g, control the air pressure to 0.7 MPa, and obtain the particles with a specific surface area of 1.5 m 2 / g.
[0143] Step S4, 200g of the crushed positive electrode material matrix was mixed with 0.3g of ZrO2, and sintered in an oxygen atmosphere furnace at 700°C for 5h, and the positive electrode material (LiNi 0.65 Co 0.15 Mn 0.2 O2).
[0144] Comparative Example 4 Step S1, dissolving metal nickel, cobalt and manganese in nitric acid at a molar ratio of 67:13:20 to form a uniform metal mixed solution, spraying and granulating the metal mixed solution, controlling the atomization flow rate to 10 L / min, controlling the median particle size D50 of the droplets to 12 μm, and the atomization temperature to 657°C to obtain the positive electrode material precursor Ni 0.67 Co 0.13 Mn 0.2 O x (0.8<x<1.2).
[0145] Step S2, weigh 500 g of the above oxide precursor and mix it evenly with 245.2 g of LiOH·H2O, and sinter the mixture in an oxygen atmosphere furnace at 920° C. for 10 hours to obtain a positive electrode material matrix.
[0146] Step S3, the positive electrode material matrix is subjected to air flow pulverization, the grinding mass is controlled at 150 g, the air pressure is controlled at 0.2 MPa, and the specific surface area of the obtained particles is 0.5 m 2 / g.
[0147] Step S4, 200g of the crushed positive electrode material matrix was mixed with 0.3g of TiO2, and sintered in an oxygen atmosphere furnace at 600°C for 6h, and the positive electrode material (LiNi 0.67 Co 0.13 Mn 0.2 O2).
[0148] The following method was used to test the performance of the positive electrode materials obtained in the above Examples 1-12 and Comparative Examples 1-4.
[0149] 1. Cell parameters: The diffraction peak of the material is tested by XRD diffractometer, with a scanning speed of 1° / min, a step length of 0.005°, and a scanning range of 10-70° to obtain the diffraction peak of the material, and then the strain value of the positive electrode material is calculated and output through XRD refinement of the diffraction peak. In the XRD refinement process, the calculation of microscopic strain and grain size is one of the key steps.
[0150] First, according to the Bragg equation and Scherrer formula, the calculation formula becomes: By analyzing β S and β D , which can be used to describe the degree of FWHM widening caused by strain. In the Rietveld refinement process, the pseudo-Voigt function is used to represent the half-height width (FWHM) of the diffraction peak function. The formula is divided into two parts: Gaussian and Lorentzian, which contain parameters related to microscopic strain and grain size respectively. The specific formula is: Gaussian part: , the Lorentz part: , where U and Y are parameters related to microscopic strain, and X and P are parameters related to grain size, which correspond to the peak shape correction parameters GU, LY, LX and GP in the refinement process. Therefore, the lattice strain parameters can be obtained by deriving the four parameters after refining the peak shape of the measured XRD data and substituting them into the corresponding calculation formula.
[0151] The XRD diffractometer was used to test the XRD images in the range of 10°-70° at 1° / min and a step length of 0.005°. The XRD images were then refined by Rietveld using GASA software, with the refinement standard being RWP < 3%. After refinement, the unit cell volume, cell parameters c, a, and cation mixing information can be obtained in the GSAS software cell parameter interface. Among them, Dp = the average value of D003 + D104.
[0152] 2. Test of microcrack ratio: Test on the proportion of particles with microcracks in positive electrode materials: First, take the powder positive electrode material, mix the powder positive electrode material with conductive carbon black and binder PVDF (polyvinylidene fluoride) in a mass ratio of 80:10:10, add NMP (N-methylpyrrolidone) to make a uniform slurry and apply it on aluminum foil, dry it in an oven, and make a pole piece. Use the pole piece as a sample, and according to the standardized process of cross-section sample preparation, use an electron transmission microscope to focus the ion beam into a small-sized ion beam to bombard the surface of the sample to achieve sample peeling. The stripped sample is tested by scanning electron microscopy (SEM). Under a field of view of 3 k, the field of view of different areas is counted, and the proportion of the number of positive electrode material particles with microcracks to the total number of positive electrode material particles is counted, and the number of microcracks is characterized by the proportion. The test results of this application are statistical results obtained by randomly selecting cross sections of about 300 positive electrode material particles in the SEM image as samples. The SEM test requires random sampling of positive electrode materials and random selection of areas. The SEM images obtained from the test can represent the average level of the positive electrode materials tested. Since the pole pieces are not rolled during the production process in this test method, the percentage of microcracks obtained from the test can be regarded as the percentage of microcrack particles in the positive electrode material in powder state.
[0153] Test on the proportion of positive electrode material particles with microcracks in positive electrode sheets: First, take the powder positive electrode material, mix the powder positive electrode material with conductive carbon black and binder PVDF (polyvinylidene fluoride) in a mass ratio of 80:10:10, add NMP (N-methylpyrrolidone) to make a uniform slurry and apply it on aluminum foil, dry it in an oven, and roll it under a pressure of 10 Mpa to make a sheet. Use the sheet as a sample, and according to the standardized process of cross-section sample preparation, use an electron transmission microscope to focus the ion beam into a small-sized ion beam to bombard the surface of the sample to achieve sample peeling. The stripped sample is tested by scanning electron microscopy (SEM). Under a field of view of 3 k, the field of view of different areas is counted, and the proportion of the number of positive electrode material particles with microcracks to the total number of positive electrode material particles is counted, and the number of microcracks is characterized by the proportion. The test results of this application are the statistical results obtained by randomly selecting the cross-sections of about 300 positive electrode material particles in the SEM image as samples. The SEM test requires random sampling of positive electrode materials and random selection of areas. The SEM image obtained from the test can represent the average level of the positive electrode material tested.
[0154] 3. The present invention uses Malvern laser particle size tester MS 3000 to test the particle volume particle size distribution of the positive electrode material. D10 represents the particle size corresponding to 10% of the cumulative particle size distribution percentage of the powder, D50 represents the particle size corresponding to 50% of the cumulative particle size distribution percentage, and D90 represents the particle size corresponding to 90% of the cumulative particle size distribution percentage.
[0155] The volume particle size distribution width of the positive electrode material = (D90-D10) / D50.
[0156] 4. Test method for atomized droplet diameter (D50): directly measure the droplet size distribution using a spray laser particle size analyzer.
[0157] 5. The test method for the tap density ρ1 of the positive electrode material is as follows: Dandong Better BT-303 was used to test the compacted density: vibration rate 3000 times / min, vibration time 1min, vibration amplitude 3mm±0.1mm.
[0158] 6. The test method for the compacted density ρ2 of the positive electrode material powder is as follows: Using the American Carver 4350 tester, 1g of sample was weighed and placed in a mold, pressed with a pressure of 3t for 30s. After pressing, the height was tested and the compacted density was calculated.
[0159] 7. The test method for the specific surface area S1 of the positive electrode material is as follows: the specific surface area of the material is tested using the McAb 3020 nitrogen adsorption method.
[0160] Finished product pretreatment: weigh the mass of the empty sample tube m1; take 3g of sample, vacuum degas at 300℃ for 1h, and weigh the mass of the sample tube m2 after cooling; sample mass m=m2-m1.
[0161] Sample testing: The sample tube is placed in liquid nitrogen, and the nitrogen adsorption capacity V of the sample is measured at a series of relative pressures P / P0 to obtain the adsorption isotherm.
[0162] The isothermal adsorption curve was fitted, and the monolayer saturated adsorption capacity Vm was calculated according to the slope and intercept; then the specific surface area was calculated according to Vm.
[0163] 8. Battery production and performance testing: a. Preparation of electrochemical performance test samples: The positive electrode material was mixed with conductive carbon black and binder PVDF (polyvinylidene fluoride) in a mass ratio of 80:10:10, and NMP (N-methylpyrrolidone) was added to make a uniform slurry. The slurry was evenly coated on aluminum foil and placed in a 100°C oven for drying for 12 hours. After drying, it was rolled at a pressure of 10 MPa and cut into circular pole pieces with a diameter of 14 mm. The negative electrode used a Li metal sheet with a diameter of 14 mm. The lithium-ion battery was assembled according to the CR2025 button battery in industry. The diaphragm was Cellgard diaphragm, and the electrolyte used an equal amount of ethylene carbonate (EC), polycarbonate (PC) and diethyl carbonate (DEC) with 1 mol / L LiPF6 as the electrolyte. The positive pole piece, diaphragm, negative pole piece and electrolyte were assembled into a button battery in an Ar gas glove box with a water content and an oxygen content of less than 0.5 ppm.
[0164] b. Power-off test: Capacity test system: The blue electric test system is used for electrical performance testing (charge and discharge voltage is 3.0~4.4V, temperature condition is 25℃), 0.1C charging, 0.1C discharging, constant voltage cut-off current is 0.005C, and the discharge capacity mAh / g is calculated.
[0165] Cycle test system: At 25°C, charge and discharge voltage is 3.0~4.4V, charge and discharge cycle is 0.5C / 1C for 100 cycles, and the final capacity retention rate after 100 cycles is the cycle performance.
[0166] 9. Gas production value test of positive electrode material: The positive electrode material, binder, conductive agent and carbon nanotubes were mixed in a mass ratio of 96:2:1.5:0.5 to make positive electrode sheets, and graphite, conductive agent and binder were mixed in a mass ratio of 95.4:1.2:3.4 to make negative electrode sheets. The separator was Cellgard separator, and the electrolyte was an equal mixture of ethylene carbonate (EC), polycarbonate (PC) and diethyl carbonate (DEC) with 1 mol / L LiPF6 as the electrolyte. They were assembled into 2Ah soft-pack batteries, stored in a high-temperature oven at 60°C for 7 days, and the gas production was tested by the drainage method.
[0167] The relevant process parameters of Examples 1-12 and Comparative Examples 1-4 are shown in Table 1, and the corresponding test results of the obtained positive electrode materials and the prepared batteries are shown in Table 2.
[0168] Table 1 Table 2 Figure 3 and Figure 4The cross-sectional SEM images of the positive electrode materials of Example 1 and Comparative Example 1 at 5000 times magnification are shown in FIG. Figure 3 and Figure 4 The locations of microcracks are marked with numbers as an example. Figure 3 It can be seen that the number of microcracks in the positive electrode material obtained in Example 1 is moderate, and 4 microcracks are marked as an example; Figure 4 It can be seen that the positive electrode material obtained in Comparative Example 1 has too many microcracks, and 7 microcracks are marked as an example.
[0169] It can be seen from Table 1-2 that the gas production of the batteries prepared with the positive electrode materials of Examples 1-12 is ≤0.9 mL / g, and the gas production of Examples 5 and 6 can be reduced to 0.2 mL / g, which is significantly lower than the gas production of Comparative Examples 1-4 (all above 1.2 mL / g). At the same time, the batteries prepared with the positive electrode materials of Examples 1-12 have a 100-week cycle retention rate of ≥87.2%, and most of them are above 90%, which is significantly higher than Comparative Examples 1-4 (the highest cycle retention rate is 86.4%).
[0170] This is because, in Examples 1-12, by regulating the sintering temperature and sintering time within a suitable range, adding a proper amount of flux, and adding the complexing agent in two steps, the crystal growth can be controlled, thereby controlling the unit cell volume V < 102.3 Å 3 , the ratio of the unit cell parameter c / a is greater than 4.95, and the proportion of microcracks in the particles in the positive electrode material is improved; by controlling the mass of the grinding body in the airflow crushing process to 0.6kg~1.8kg and the crushing air pressure to 0.4Mpa~0.65Mpa, the proportion of particles with microcracks in the positive electrode material can be controlled to be 1.5%~11%, which can effectively improve the gas production problem of the positive electrode material and reduce the gas production of the prepared battery. At the same time, it can improve the structural stability of the positive electrode material, thereby improving the cycle performance of the prepared battery.
[0171] It can be seen from Examples 1, 3 and 4 that as the atomization temperature decreases, the unit cell volume in the positive electrode material decreases, the proportion of particles with microcracks in the positive electrode material remains basically the same, but the gas production of the positive electrode material increases, indicating that a too small unit cell volume may lead to a decrease in the strength of the grains, making it difficult to suppress the expansion of microcracks in the grains during the cycle.
[0172] It can be seen from Example 1 and Example 9 that Example 1 adopts one-time sintering, while Example 9 adopts segmented sintering. The unit cell volume of the positive electrode material is basically the same, but the proportion of particles with microcracks in the positive electrode material of Example 9 is significantly reduced compared with Example 1. This is because, during the segmented sintering process of Example 9, the low-temperature sintering stage is conducive to the uniform diffusion of the flux in the mixture, and is more conducive to bridging the intercrystalline cracks of the crystal, so that the final sintered material becomes rounded and dispersed crystal particles. In addition, the rapid annealing and cooling in the later stage of the segmented sintering of Example 9 can further repair the intercrystalline cracks, thereby effectively reducing the proportion of microcracks in the particles.
[0173] It can be seen from Example 1 and Example 10 that as the amount of grinding body increases, the unit cell volume in the positive electrode material is basically the same, but the proportion of particles with microcracks in the positive electrode material increases significantly. This is because the increase in the amount of grinding body causes more microcracks in the positive electrode material due to excessive collisions of particles.
[0174] However, the sintering process parameters of Comparative Examples 1-4 are not within the aforementioned range, and no flux or complexing agent is used. The unit cell volume V of the prepared positive electrode material is greater than 102.3 Å. 3 , the unit cell volume is too large to reduce the strength and toughness of the lattice, so that the material is prone to lattice defects when subjected to alternating stress, resulting in microcracks in the crystal, which may become a sensitive point for electrochemical corrosion, increase the probability of side reactions with the electrolyte, increase gas production, and affect the cycle life of the battery, and the ratio of the unit cell parameter c / a of the positive electrode material is less than 4.95, the ratio of the unit cell parameter c / a is small, the layered structure defects increase, and the diffusion degree of microcracks will increase during the battery charging and discharging process, increase the battery gas production, and affect the cycle life. In addition, the airflow crushing process of Comparative Examples 1-4 is not within the specified range, and the proportion of single crystal microcracks in the prepared positive electrode material exceeds 11%, and there are too many crystal cracks. After such positive electrode materials are prepared into batteries, the battery gas production will be significantly deteriorated during the cycle.
[0175] The above implementation modes are only used to illustrate the technical solutions of the present application and are not intended to limit the present application. Although the present application has been described in detail with reference to the above preferred implementation modes, a person skilled in the art should understand that the technical solutions of the present application may be modified or replaced by equivalents without departing from the spirit and scope of the technical solutions of the present application.
Claims
1. A positive electrode material, characterized in that: The general formula of the positive electrode material is as follows: Li x Ni a Co b M c N d O2, M is Mn or Al, N is a metal element, wherein 0.98≤x≤1.1, 0.60≤a≤0.70, 0.06≤b≤0.12, 0.20<c≤0.32, 0<d≤0.10, a+b+c+d=1; the ratio of the number of particles with cracks in the positive electrode material to the total number of particles is 1.5%~11%, and the unit cell volume V of the positive electrode material is less than 102.3 Å 3 , the unit cell parameters of the positive electrode material satisfy: the ratio of c / a is greater than 4.
95.
2. The positive electrode material according to claim 1, characterized in that The unit cell volume satisfies: 98.6 Å 3 <V<102.3Å 3 , the unit cell parameters satisfy: 2.7584≤a≤2.8790 Å, 13.2865≤c≤14.2550 Å.
3. The positive electrode material according to claim 1, characterized in that The proportion of Li / Ni mixed arrangement in the positive electrode material is 5% to 8%.
4. The positive electrode material according to claim 1, characterized in that The lattice strain of the positive electrode material is less than 0.2%.
5. The positive electrode material according to claim 1, characterized in that The unit cell parameter Dp of the positive electrode material measured by XRD is 80nm~110nm.
6. The positive electrode material according to claim 1, characterized in that The positive electrode material is a single crystal positive electrode material, which contains single crystal grains with the same orientation, and the average grain size of the single crystal grains is 1 μm to 5 μm.
7. The positive electrode material according to claim 1, characterized in that The positive electrode material satisfies at least one of the following characteristics: (1) The particle size distribution width of the positive electrode material satisfies L=(D90-D10) / D50≥1.0; (2) The specific surface area of the positive electrode material is 0.5 m 2 / g~1.2 m 2 / g; (3) The tap density of the positive electrode material is ρ1>1.8 g / cm 3 ; (4) The compaction density of the positive electrode material is ρ2>3.00g / cm 3 .
8. A method for preparing a positive electrode material, characterized in that: The following steps are involved: The nickel source, cobalt source and manganese source solutions are mixed, atomized and then thermally decomposed to obtain a precursor; The precursor, lithium source and flux are mixed and sintered to obtain a positive electrode material matrix; The positive electrode material matrix is crushed, wherein the ratio of the number of particles with cracks in the crushed positive electrode material matrix to the total number of particles is 1.5% to 11%; and The crushed cathode material substrate is coated and post-processed to obtain the cathode material, wherein the unit cell volume V of the cathode material is less than 102.3 Å 3 , the unit cell parameters satisfy: the ratio of c / a is greater than 4.
95.
9. A positive electrode sheet, characterized in that: A positive electrode material comprising the positive electrode material as described in any one of claims 1 to 7 or prepared by the method for preparing the positive electrode material as described in claim 8, wherein, in the positive electrode sheet, the number of particles of the positive electrode material having the cracks accounts for 1.5% to 11% of the total number of particles of the positive electrode material.
10. A secondary battery, comprising a housing, an electrode assembly, and an electrolyte or an electrolyte, wherein the electrode assembly and the electrolyte or the electrolyte are both located in the housing, and the electrode assembly comprises a separator and a negative electrode sheet, characterized in that: The electrode assembly also includes a positive electrode sheet, the isolation membrane is arranged between the positive electrode sheet and the negative electrode sheet, and the positive electrode sheet includes the positive electrode material as described in any one of claims 1 to 7 or the positive electrode material prepared by the method for preparing the positive electrode material as described in claim 8.
Citation Information
Cited By
Positive electrode active material precursor and preparation method thereof, positive electrode active material, positive electrode plate, battery and electric equipment
CN121085328A